TOWARDS HARMONIZATION FROM DISPUTE RELATIONSHIP BETWEEN WORKERS AND ENTERPRISES THROUGH CASE INSPECTIONS IN THE FAST INDUSTRIAL RELATIONSHIP, FAIR AND CHEAP - Hono Sejati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
The problems studied in this research are (1) Why is the examination of PHI case not yet fast, fair and cheap? (2) What are the obstacles in the examination of cases in the IRC that have not been fast, fair and cheap? (3) How is the examination of the case in PHI based on the value of fast, fair and cheap? The research method used sociological juridical approach. Technique of collecting data by interview, observation, and documentation. The results of the study concluded (1) The examination of the case in the IRC has not been fast, fair and cheap due mainly to differences in perception of Lawmakers with the parties. (2) Obstacles to the examination of a PHI case are: filing a lawsuit, longer invitation because the defendant's residence is outside the legal area of the IRC, the defendant has died, the company is not operational, the lack of control of the union administrator, (3) in PHI based on the value of fast, fair and cheap is by consensus consensus